2022
DOI: 10.1371/journal.pone.0276704
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CG17003/leaky (lky) is required for microtubule acetylation in early germ cells in Drosophila ovary

Abstract: Microtubule acetylation is found in populations of stable, long-lived microtubules, occurring on the conserved lysine 40 (K40) residue of α-tubulin by α-tubulin acetyltransferases (αTATs). α-tubulin K40 acetylation has been shown to stabilize microtubules via enhancing microtubule resilience against mechanical stress. Here we show that a previously uncharacterized αTAT, Drosophila CG17003/leaky (lky), is required for α-tubulin K40 acetylation in early germ cells in Drosophila ovary. We found that loss of lky r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…FCs expressing germline determinants were thought to alter their cell fate and fail to properly specify FC subtypes [40]. Consistent with these reports, we found that shg RNAi and dCR4h ovaries exhibit fused egg chambers accompanied with ectopic expression of laminC, the marker of stalk cells, in main body FCs (Figure 4, Figure S2).…”
Section: Loss Of E-cadherin Results In Cytoplasmic Leakage Between Fc...supporting
confidence: 89%
See 3 more Smart Citations
“…FCs expressing germline determinants were thought to alter their cell fate and fail to properly specify FC subtypes [40]. Consistent with these reports, we found that shg RNAi and dCR4h ovaries exhibit fused egg chambers accompanied with ectopic expression of laminC, the marker of stalk cells, in main body FCs (Figure 4, Figure S2).…”
Section: Loss Of E-cadherin Results In Cytoplasmic Leakage Between Fc...supporting
confidence: 89%
“…Previous reports have demonstrated that the misexpression or mislocalization of germline gene products in FCs results in cyst or egg-chamber individualization defect, where two or more germline cysts are surrounded by a single FC epithelium [39] [40].…”
Section: Loss Of E-cadherin Results In Cytoplasmic Leakage Between Fc...mentioning
confidence: 99%
See 2 more Smart Citations